2015
DOI: 10.1097/phm.0000000000000300
|View full text |Cite
|
Sign up to set email alerts
|

Physical Trauma and Infection as Precipitating Factors in Patients with Fibromyalgia

Abstract: One-fourth of this study's patients with fibromyalgia had precipitating physical trauma or infection. Patients with precipitating infection had different sociodemographic characteristics, clinical presentation, and quality-of-life from the idiopathic and trauma groups. Further studies are needed to look into the relationships between precipitating events and fibromyalgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 21 publications
2
32
3
Order By: Relevance
“…These data indicate that the possible association between FQs and fibromyalgia is possibly due to the viral or bacterial infection for which they are prescribed. This is corroborated by a number of studies that have shown that fibromyalgia might be triggered by an infectious process [6]. Our data is corroborated by inclusion of azithromycin, an antibiotic generally prescribed for more severe respiratory community-acquired infections.…”
Section: Discussionsupporting
confidence: 87%
“…These data indicate that the possible association between FQs and fibromyalgia is possibly due to the viral or bacterial infection for which they are prescribed. This is corroborated by a number of studies that have shown that fibromyalgia might be triggered by an infectious process [6]. Our data is corroborated by inclusion of azithromycin, an antibiotic generally prescribed for more severe respiratory community-acquired infections.…”
Section: Discussionsupporting
confidence: 87%
“…The importance of the present study relies in that it shows, for the first time, that the activation of transposable elements, in particular some HERV sequences, is a mechanism linked to FM, potentially explaining the reasons for repeated failures in detecting exogenous infectious agents as etiologic triggers of the disease and for the flu-like symptoms patients experience [11][12][13][14]. Because of the reduced sample size and the limitation for identifying specific activated genomic loci with the method used, detection of molecular differences between FM patients suffering or not of comorbid ME/CFS was not possible.…”
Section: Discussionmentioning
confidence: 93%
“…Although separate clinical diagnostic criteria are described for FM and ME/CFS [2,3,[6][7][8][9][10], common features such as alterations of the immune system and overlapping symptoms such as flu-like symptoms are described [11,12]. As such, many authors have investigated a possible viral etiology of the disease [13,14]. However, no clear correlation between FM or ME/CFS and viral infection has yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…HLA genes have an essential role in the immune system. Thus, the emerging picture is that a combination of genetic predisposition, a precipitating event (infections, trauma, autoimmune diseases or other reasons of necrosis) (Jiao et al, 2015), and immune dysregulation due to psychological stress (Takahashi et al, 2018) may convert autotolerance or pre-existing occult autoimmunity into overt autoimmunity, but the autoreactive component remains elusive (Figure 1). Importantly, though the precipitation event may be transitory, autoimmunity is a response of the adaptive immune system and is chronic.…”
Section: Fibromyalgia: Introducing the Autoimmune Hypothesismentioning
confidence: 99%